2020
DOI: 10.9758/cpn.2020.18.1.164
|View full text |Cite|
|
Sign up to set email alerts
|

Low-dose Quetiapine-induced Syndrome of Inappropriate Antidiuretic Hormone in a Patient with Traumatic Brain Syndrome

Abstract: Syndrome of inappropriate antidiuretic hormone secretion (SIADH) is characterized by hyponatremia, low serum osmolality, and clinical euvolemia in the absence of diuretic medication. And the causes of SIADH are various, antipsychotic agents and traumatic brain injury (TBI) are well known. Quetiapine is often chosen to manage the maladaptive behavior of patients with post-TBI. Although a previous study reported that quetiapine doses ranging from 25 to 300 mg were effective and tolerable, the symptoms of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The mechanism of intracranial hemorrhage associated with hyponatremia may be related to brain natriuretic factors, probably secreted by the thalamus 15 . Kang et al 16 also reported a case of low-dose quetiapine-induced SIADH with a history of traumatic subdural hemorrhage. Thus, a history of traumatic subdural hemorrhage may be a precipitating factor for the development of hyponatremia when patients are exposed to antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of intracranial hemorrhage associated with hyponatremia may be related to brain natriuretic factors, probably secreted by the thalamus 15 . Kang et al 16 also reported a case of low-dose quetiapine-induced SIADH with a history of traumatic subdural hemorrhage. Thus, a history of traumatic subdural hemorrhage may be a precipitating factor for the development of hyponatremia when patients are exposed to antipsychotics.…”
Section: Discussionmentioning
confidence: 99%